Sistem Informasi Penjualan Tiket Berbasis Mobile Menggunakan Pemodelan UML Studi Kasus Waterboom - Widhiyanti, Rahayu; Voutama, Apriade (Jurnal Sains dan Teknologi (JSIT), 2026)
The use of technology in the business sector can significantly improve organizational effectiveness and efficiency. A waterboom is one of the tourism businesses that is highly popular among the public. One of the main problems encountered in the manual ticket purchasing process is long queues, especially during long holiday periods when the number of visitors increases, resulting in ticketing congestion. This condition leads to inefficiencies and reduces visitor convenience. Therefore, it is necessary to develop a waterboom information system that not only provides information about waterboom facilities but also enables online ticket purchasing, so that visitor queues can be reduced and ticket accumulation can be avoided. In addition, the system can assist management in monitoring and managing ticket sales more effectively. In designing the infrastructure of a mobile-based application system, Unified Modeling Language (UML) is used as a design modeling tool. UML is a visual modeling language that supports the system design process and helps minimize errors during application development. The proposed ticketing application is developed using several technologies, including Eclipse as an integrated development environment (IDE) for smartphone platforms, PHP (Hypertext Preprocessor) as the programming language, and MySQL as the database management system.